On the use of artificial neural networks for biomedical applications - Ruano, M. Graça (2013)
Artificial Neural Networks (ANN) are being extensively used in many application areas due to their ability to learn and generalize from data, similarly to a human reaction. This paper reports the use of ANN as a classifier, dynamic model, and diagnosis tool. The examples presented include blood flow emboli classification based on transcranial ultrasound signals, tissue temperature modeling based on imaging transducer’s raw data and identification of ischemic cerebral vascular accident areas based on computer tomography images. In all case studies the performance of ANN proves to produce very accurate results, encouraging the more frequent use of these computational intelligent techniques on medical applications.